Peran Peradilan Islam dalam Penegakan Hukum Islam di Kesultanan Buton - asni, Asni (al-'adalah, 2017)
This article tries to reveal the existence of the Islamic Courts in the Sultanate of Buton to measure the extent of its role in the enforcement of Islamic Law in the past. History explains that when Islam entered the territory of Southeast Sulawesi, the kingdom of Buton changed its status to Buton Sultanate and applied Islamic law throughout the empire. Using historical approach, the researcher succeeded in revealing the fact that in the area of the past Sultanate of Buton, once stood two institutions of Islamic Court named Syarana Adati and Syarana Hukumu or Syarana Agama. The authority of Syarana Adati was to deal with criminal cases where as Syarana Hukumu or Syarana Agama took care of certain civil cases such as marriage, divorce and inheritance. Despite the separation of authority, the two institutions can be categorized as Islamic Courts because the legal system used as a backdrop was Islamic Law. The study also finds out that the two institutions play a significant role in the upholding of Islamic law in the past as they were supported by the kingdom, and a strong legal culture both among law enforcers and in the community